(3TQM QSGdI aj BOGH GdHMKs - (3eLghds ((3eMeO Hf SdjeGfs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg QH GdYGdejf hHYO adeG cGf gPg GdQSGdI ZjQ eTQhMI TQMJgG eY bdI GdHVGYI aj GdYde GYde Gf GdfSH GdeYGfj CQHYI GdJSGhj hGdYehe hGdNUhU eWdb s
(3BNQgG (B:s
(3agh Cf jLYd CMO GdTjFjf ehVhYG hGdBNQ eMehdG cbhdfG GdEfSGf djS HLeGO hEf cGf aj ReGffG jcGO Cf jchfG eJUGObjf LRFjGs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3GdMhGTj h GdJYdjbGJ (B:s
(3JYdjbGJs
Keywords: (3GdadSaI hGdefWbs